ANALISIS KUALITAS BUKU TEKS MATEMATIKA SMK KELAS XI KURIKULUM 2013 EDISI REVISI TAHUN 2017 BERDASARKAN PENDEKATAN SAINTIFIK - Muh. Alwan Haris; Andi Kusumayanti; Muliaty Amin; Andi Dian Angriani; Nidya Nina Ichiana (Faculty of Tarbiyah and Teacher Training, 2022)
This study discusses the quality of Mathematics Textbooks for Class XI Curriculum 2013 Revised 2017 Edition based on a scientific approach. This study aims to find out how the quality of the mathematics textbook is based on indicators in a scientific approach which include: (1) observing, (2) asking questions, (3) digging for information, (4) associating/reasoning and (5) communicating. This research is a quantitative descriptive study that displays the results of the data as they are without any manipulation or other treatment. The procedure in this study consisted of: (1) the preparation stage, by selecting the textbook to be analyzed in this case the researcher took the 2013 Revised 2017 Edition of the Mathematics Textbook of the Ministry of Education and Culture, (2) then collected data using document analysis techniques and carried out literature study using pre-determined instruments, to find out how the quality of the mathematics textbook is based on a scientific approach, (3) drawing conclusions from the data that has been obtained. Chapter I is 60%, Chapter II is 70%, Chapter III is 56%, and Chapter IV is 73%. As for the total number of chapters in the mathematics textbook of SMK class XI semester I, the percentage of quality textbooks based on the scientific approach is 64.75%. So, it can be concluded that the quality of mathematics textbooks for class XI curriculum 2013 based on the scientific approach is included in the